IMPLEMENTATION OF MULTICULTURAL VALUES IN CIVICS LEARNING WITH LITERACY MEDIA IN ELEMENTARY SCHOOL - Ana Nurhasanah; Arita Marita; Arifin Maksum (JPSD (Jurnal Pendidikan Sekolah Dasar), 2021)
AbstractThis research aims to describe multicultural values in Civics learning using literacy media at SDN Bahayangkari, Serang City. This research was conducted using a narrative method with interview techniques (Cresswell, 2012). The subjects of this research were fourth grade teachers at SDN Bhayangkari 1 Serang, Banten. Data were collected through interviews and documentation. The results showed that the implementation of multicultural values in Civics learning with literacy media as follows 1) Learning outcomes were guided on the students' competence, 2) the quality of the learning approach selection is carried out according to the curriculum; 3) techniques for organizing material is suitable to the learning objectives; 4) proper use of literacy media and 5) appropriateness of assessment techniques. The implementation of multicultural values in Civics learning with literacy media is through these following activities 1) systematic learning steps; 2) introducing cultural diversity according to basic competencies; 3) the use of source books and learning media that present messages introducing the diversity that exists in the school environment. Thus students' understanding of multicultural values can be demonstrated through positive behavior in the diversity of nation tribes, ethnicities, religions, and cultures.Keywords: Multicultural Values; Civics Learning; Media literacy